Mosaic KCNJ2 mutation in Andersen–Tawil syndrome: targeted deep sequencing is useful for the detection of mosaicism. (6th March 2014) - Hasegawa, K.; Ohno, S.; Kimura, H.; Itoh, H.; Makiyama, T.; Yoshida, Y.; Horie, M.
<x xml:space="preserve">Abstract</x> Andersen–Tawil syndrome (ATS) is an inherited disease characterized by ventricular arrhythmias, periodic paralysis, and dysmorphic features. It results from a heterozygous mutation of KCNJ2, but little is known about mosaicism in ATS. We performed genetic analysis of KCNJ2 in 32 ATS probands and their family members and identified KCNJ2 mutations in 25 probands, 20 families who underwent extensive genetic testing. These tests revealed that seven probands carried de novo mutations while 13 carried inherited mutations from their parents. We then specifically assessed a single proband and the respective family. The proband was a 9 year old girl who fulfilled the ATS triad and carried an insertion mutation (p.75_76insThr). We determined that the proband's mother carried a somatic mosaicism and that the proband's younger brother also carried the ATS phenotype with the same insertion mutation. The mother, who exhibited mosaicism, was asymptomatic, although she exhibited Q(T)U prolongation. Mutant allele frequency was 11% as per TA cloning and 17.3% as per targeted deep sequencing. Our observations suggest that targeted deep sequencing is useful for the detection of mosaicism and that the detection of mosaic mutations in parents of apparently sporadic ATS patients can help in the process of genetic counseling.